Emancipation of dalits and freedom struggle - Sadangi, H.C. (Delhi, 2008)
The book analyses political and social transition at the juncture of Indian Independence in 1947 from the British to Indians, with a view of Dalits, who got initial emancipation under the British rule from Hindu Varna system and Brahmanical Tyranny. The book highlights the issues of untouchability, Mahar Movement, Mahatma Gandhi, Mahatma Phule and Dr. B.R. Ambedkar.
Keywords: Dalit